Les préliminaires textuels de Robert Browning - Yann Tholoniat (Cahiers Victoriens et Edouardiens)
From his first poems onwards, Browning displayed a great interest in paratextual strategies—« from title page to closing line », as is said in his poem « Sibrandus Schafnaburgensis » (Dramatic Romances and Lyrics, 1845). Indeed, this peripheral zone or textual threshold is very important: it settles a pact between the poet and his reader and testifies to the author’s control over his text. In the paratext—and especially in the titles, subtitles and epigraphs—Browning’s endeavour is twofold: the poet teases the reader and he tries to channel or rather tune up the speaker’s voice by means of various combinations of a number of paratextual elements. Hence, Browning’s paratexts appear clearly as the place where a dialogue between the reader and the poet is to be heard, and as the necessary preliminaries enabling Browning to endow each speaker with identifiable inflections.